Introducing the Condor Array Telescope. VI. Discovery of Extensive Ionized Gaseous Filaments of the Cosmic Web in the Direction of the M81 Group - Kenneth M. Lanzetta; Stefan Gromoll; Michael M. Shara; David Valls-Gabaud; Frederick M. Walter; John K. Webb (The Astrophysical Journal)
We used the Condor Array Telescope to obtain deep imaging observations through luminance broadband and He ii , [O iii ], He i , H α , [N ii ], and [S ii ] narrowband filters of an extended region of the M81 Group spanning ≈8 × 8 deg ^2 on the sky centered near M81 and M82. Here, we report aspects of these observations that are specifically related to (1) a remarkable filament known as the “Ursa Major Arc” that stretches ≈30° across the sky roughly in the direction of Ursa Major, (2) a “giant shell of ionized gas” that stretches ≈0.8 deg across the sky located ≈0.6 deg northwest of M82, and (3) a remarkable network of ionized gaseous filaments revealed by the new Condor observations that appear to connect the arc, the shell, and various galaxies of the M81 Group and, by extension, the group itself. We measure flux ratios between the various ions to help to distinguish photoionized from shock-ionized gas, and we find that the flux ratios of the arc and shell are not indicative of shock ionization. This provides strong evidence against a previous interpretation of the arc as an interstellar shock produced by an unrecognized supernova. We suggest that all of these objects, including the arc, are associated with the M81 Group and are located at roughly the distance (≈3.6 Mpc) of M81, that the arc is an intergalactic filament, and that the objects are associated with the low-redshift cosmic web.